Transcriptomic characterization of GMP-compliant regulatory macrophages (TRI-001) under inflammatory and hypoxic conditions: a comparative analysis across macrophage subtypes - Karina Zitta; Rouven Berndt; Katharina Hess; Fred Fändrich; Olga Gurvich; Katja Sirviö; Tuija Kekarainen; Lars Hummitzsch; Yuk Lung Wong; Ole Sattler; Steven Braem; Mark Krebs; et al. (Journal of Translational Medicine)
Abstract Background Regulatory macrophages (Mreg) represent a unique subset of macrophages known for their angiogenic and anti-inflammatory properties, positioning them as promising candidates for cell-based therapies. Recently, we have differentiated and characterized a distinct Mreg subtype (TRI-001), which is currently being produced in accordance with good manufacturing practice (GMP) for a multicenter study aimed at treating patients with peripheral arterial occlusive disease (PAOD). Aim of the Study To compare the transcriptome of TRI-001 with various in vitro differentiated macrophage subtypes to provide a comprehensive context for TRI-001 within the macrophage landscape. Additionally, we aimed to develop a detailed transcriptome profile of TRI-001 under transient hypoxic and inflammatory conditions, mimicking the microenvironment in PAOD patients. Methods Mreg were differentiated from human CD14 + monocytes using a GMP-compliant protocol and identified as TRI-001 by flow cytometry. Hypoxia was induced via an enzymatic model, while LPS treatment of TRI-001 was employed as inflammatory stimulus. Transcriptomic profiling was conducted using the Illumina HiSeq 4000 platform. In vitro cell migration assays (Oris assays) were conducted using human umbilical vein endothelial cells (HUVEC) cultured with supernatants derived from normoxia and hypoxia treated TRI-001. Results TRI-001 demonstrated significant transcriptomic similarities with Mreg and Mreg_UKR but were different from M0, M1, M2a, and PCMO subtypes. Under hypoxic conditions and LPS stimulation, TRI-001 displayed distinct gene expression profiles compared to TRI-001 under control conditions, with hypoxic and LPS-stimulated profiles showing notable overlap. Pathway enrichment analysis suggested the activation of chemotaxis and migration-associated pathways especially under hypoxic conditions. Findings from functional in vitro cell migration assays were inconclusive, as the secretome of TRI-001, whether cultured under hypoxic or normoxic conditions, did not elicit a significant effect on endothelial cell migration. Conclusion TRI-001 represents a novel type of regulatory macrophages (Mreg). The distinctive transcriptional responses to hypoxia and inflammatory stimuli highlight its potential as a cell therapy for the treatment of PAOD patients.